PENTINGNYA PEMAHAMAN KEPALA PERANGKAT DAERAH TERHADAP JABATAN FUNGSIONAL DALAM MENINGKATKAN KINERJA PEMERINTAH KABUPATEN KARIMUN - Suci Suriani; Andika Prasetya; Wan Arif Hidayatullah; Bobby Arifin (Jurnal Transformasi Administrasi, 2025)
This study investigates the comprehensive impact of the understanding of the heads of regional apparatus on functional positions, the management of functional roles, and performance enhancement strategies on the overall performance of the Karimun Regency Government. A well-informed leadership on functional positions is expected to increase bureaucratic efficiency and elevate public service delivery. The findings reveal that the understanding of functional roles, the optimization of these positions, and systemic efforts toward performance improvement each significantly affect governmental performance. Collectively, these three factors account for 82.7% of the variation in government performance, emphasizing the importance of synergy among them. Thus, it is concluded that a holistic approach (encompassing leadership insight, structured functional role management, and continuous performance improvement) is essential for achieving effective and responsive local governance.